2009
DOI: 10.1063/1.3086898
|View full text |Cite
|
Sign up to set email alerts
|

Integrated plasmonic lens photodetector

Abstract: We present a fabricated metal-semiconductor-metal ͑MSM͒ photodetector exhibiting an enhanced photocurrent by integrating a nanoscale metallic grating into its contacts. This serves to increase the incident photon flux about the aperture of the device by guiding incident photons as surface plasmon polaritons. High speed time response data shows that the device responsivity may be increased without sacrificing speed. We demonstrate both a photocurrent enhancement and responsivity increase of about 90% at the des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 14 publications
0
49
0
Order By: Relevance
“…Figure 3 illustrates a plasmonic-based MSM-PD structure, which consists of three separate layers, namely, (i) a top layer (metal nanograting), (ii) an unperturbed metal layer (underlayer) containing conventional sub-wavelength apertures, and (iii) a semiconductor (GaAs) substrate. For a metal nanograting with the period of Λ, the wave vector of the excited SPPs (k sp ) is given by [1,[8][9][10][11] …”
Section: Experimental Observation Of Nanograting Phase Shift In Msm-pdmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 illustrates a plasmonic-based MSM-PD structure, which consists of three separate layers, namely, (i) a top layer (metal nanograting), (ii) an unperturbed metal layer (underlayer) containing conventional sub-wavelength apertures, and (iii) a semiconductor (GaAs) substrate. For a metal nanograting with the period of Λ, the wave vector of the excited SPPs (k sp ) is given by [1,[8][9][10][11] …”
Section: Experimental Observation Of Nanograting Phase Shift In Msm-pdmentioning
confidence: 99%
“…Based on finite-difference time-domain (FDTD) simulation, results have shown significant enhancement of light absorption through interaction with surface plasmon polaritons (SPPs) for the design of MSM-PDs [1,[5][6][7][8][9][10][11]. In this paper, the FDTD method is used to simulate the light absorption enhancement in a GaAs MSM-PD structure, wherein the metal fingers are structured to form a metal nanograting above an unperturbed part of the metal fingers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A carefully designed nano-antenna positioned on top of a photodetector, which is smaller in size than the wavelength of the incident light, can be used to collect more photons. There are many experimental and computational examples reported for such devices from the near-IR to visible spectrum [2][3][4][5][6][7][8]. However, there is not many research reported on plasmonic structures in the UV region.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Plasmonic structures for the enhancement of absorption and the concentration of light into nanoscale volumes have been studied theoretically [14][15][16] and experimentally. 17,18 Dipole antennas have been demonstrated to enhance the optical cross sections of Ge nanophotodetectors. 19 Of particular practical interest is the use of a plasmonic bull's eye structure (BES), that is, a concentric plasmonic grating surrounding a nanohole aperture, 20,21 as such a structure can capture light from a large area and concentrate it into a nanoscale aperture.…”
Section: Introductionmentioning
confidence: 99%